Cancer and hereditary haemorrhagic telangiectasia - Hosman,AE; Shovlin,CL (Journal of Cancer Research and Clinical Oncology, 2016)
ObjectiveTo examine associations between cancer incidence and hereditary haemorrhagic telangiectasia (HHT).MethodsTwo studies with contrasting conclusions were compared. The first had used a registry-based, matched-pairs approach, while the second utilised HHT family-based, survey methodology.ResultsThe first manuscript captured data on cancer incidence in a total of 316,581 matched cancer patients–non-cancer controls, which included 431 HHT cases. No association was found between HHT and pooled cases of lung, breast, prostate, and colorectal cancer (adjusted OR 0.978, 95% CI [0.795, 1.204]). The second, which was powered to examine these four cancers individually, captured data from 2161 HHT cases and 2817 related controls. Fewer HHT-affected individuals had cancer (398/2161, [18.4%]) compared to 668/2817 (23.7%) related controls (p = 0.0012). Of the four most common cancers, prostate and colorectal cancer rates were equivalent, but lung cancers were significantly less frequent in HHT (adjusted OR 0.48 [0.30, 0.70], p = 0.0012), and breast cancer was more frequent (adjusted OR 1.52 [1.07, 2.14] p = 0.018).ConclusionsThe respective studies had different methodological strengths and weaknesses. Potential reasons for the discrepant conclusions include study power, particularly important to dissect specific cancers where differential contributions from HHT genotypes and environmental confounders might be predicted.